(untitled) (Proceedings of International Educators Conference, 2024)
In this article, relevant pedagogical recommendations on the issues of increasing the socio-spiritual potential of future elementary school teachers and forming an active citizenship position, as well as the issues of attention given to them, have been disclosed.